Anodização para obtenção de membranas cerâmicas - Timoteo Júnior, José Flávio (2007)
This a study on the achievement of alumina membranes by the method of anodizing. From this method got up a layer of aluminum oxide on the anodic metal, who presented the basic properties necessary for the application as a support for the production and acquisition of nanomaterials, such as porosity nano and resistance to high temperature, and other properties, as resistance to corrosion, and chemical, high ranking of the structure and pore size of the pores. The latter, ranging from 10 to 100nm depended on the electrolyte used, which in this study was the H2SO4. To remove all remaining aluminum, it is a bath of dissolution with HCl and CuCl where the residual aluminum has been withdrawn, and the deep pores were opened after chemical treatment with NaOH. After the dissolution, the membranes were calcined at temperatures of 300, 600 and 900° C, and sintered at temperatures of 1200 and 1300º C to win mechanical strength, porosity and observe the desired crystallization. Then went through analyses of composition through X-ray diffraction and morphology of the microstructure through a scanning electron microscope. The method was effective for obtaining alumine membranes applied in the processes of production of materials in nano